Role of ultrasonographic findings with clinical and laboratory findings in identification of intra and extra testicular causes of male infertility (Journal of Pharmaceutical Negative Results, 2022)
Background: It has been estimated that almost 7% of men in their reproductive age are sub-fertile or infertile due to pre-testicular, testicular or post-testicular problemsObjective: Materials & Methods: This prospective study was carried out in 100 male patients attending the outpatient department of Infertility clinic of Department of Surgery, Jawaharlal Nehru medical college and hospital over a period of 18 months.Results: We have found an uneven distribution of testicular volume among various sonographic conditions. Although testicular volume was below normal in all abnormal sonographic conditions. Patients with normal sonographic scans had largest testicular volume. Most sonographic abnormalities including varicocoele, atrophic testes, epididymal cyst were common in 25-30 years age group. Absent testes, testicular microlithiasis and bulky seminal vesicle were not found in any specific age groups as the numbers of patients of those sonographic abnormalities were quite less.Conclusion: This study emphasizes that colour Doppler ultrasonography is a very sensitive investigation in detecting various abnormalities that were often missed by repeated clinical examinations.